(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Aimed at the researcher during his research to characterize the elements of internal control under the standards of the state and measurement and analysis of the extent to which those elements in the form of technical education through a selected sample included the three institutes (Institute of Directors Technical Institute for the preparation of the trainees and the Institute of Technology). The researcher used the method of analysis the descriptive terms used questionnaire to collect the necessary information and were subject to analysis using descriptive statistical methods Kalost mean and standard deviation, and research found a set of conclusions, including a commitment to the elements of internal control in the form of technical education, but not significantly and more institutions committed to the Institute of Technology and Management Institute technical and finally Institute to prepare the trainees, In the light of the results of research the researcher presented some of the recommendations including the need to interest the recent developments in the field of internal control in accordance with international standards through policies and procedures to adopt.